Impact of surface roughness on long-term candida biofilm colonization of prosthetic silicone: A pilot study. Issue 1 (2014) - Leonhard, M; Zatorska, B; Moser, D; Bertl, K; Bigenzhan, W; Schneider-Stickler, B
No abstract available